A comprehensive review of the thermal oxidation stability of jet fuels. (16th January 2021) - Jia, Tinghao; Zhang, Xiangwen; Liu, Yi; Gong, Si; Deng, Chuan; Pan, Lun; Zou, Ji-Jun
Graphical abstract: Abstract: In current aircraft designs, jet fuel serves a dual role as a coolant to satisfy the cooling requirements and as a propellant to provide propulsion power, especially in high-performance aircraft. Importantly, thermal oxidative stability is one of the key issues for jet fuels that serve as coolants since the formation of deposits during heat exchange will directly influence the operational safety of the aircraft. This review summarizes the research progress on the thermal oxidation and deposition of jet fuel during autoxidation, with particular emphasis on the research performed over the past few decades. The precise concept of thermal oxidative stability is first introduced. Then, the oxidation and deposition mechanisms of jet fuel and the corresponding reaction kinetics during thermal stress are comprehensively summarized. After that, different evaluation techniques (oxidation and deposition), as well as the factors influencing the thermal oxidative stability of jet fuel (chemical and physical factors), are presented in detail. Finally, the corresponding improvement methods for delaying fuel oxidation and mitigating deposition are proposed. This review will be beneficial for the design of jet fuel with high thermal oxidative stability and the further development of high-performance aircraft.